Mediterranean imports. Real influence on the civilization of the Celtic Central Europe during the 6th-5th century BC or only a diffusion of exongeus artefacts? - Trefný, Martin Josef
The article presents several thoughts on the relationships between Central Europe during the Early Iron Age and the Mediterranean area on the example of four selected criteria. The article focuses on the problems of urbanism and centralisation, Greek symposion and its hypothetical reflection in the Transalpine Central Europe, adoption of some forms of the material culture and finally on the problems connected to the wall paintings in the funeral contexts. The article presents the conclusion that the influence of the Mediterranean world on most substantial aspects of the contemporary life in Central Europe is perceptible only in some categories, whereas the overall influence of the Mediterranean area on the indigenous Central European communities during the Early Iron Age is marginal.
Keywords: influence; Mediterranean; Central Europe